PENGARUH CORPORATE GOVERNANCE DAN KARAKTERISTIK PERUSAHAAN TERHADAP SUSTAINABILITY DISLOSURE (Studi Kasus pada Perusahaan Sektor Food and Beverages yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023) - Ramanda Putra Pratama; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2025)
This research refers to research by (Indrianingsih 2020) that examines the effect of company size, financial performance, and corporate governance on the sustainability report of non financial companies listed on the Indonesia Stock Exchange in 2013-2017. This research aims to examine the influence of corporate governance and company characteristic on corporate sustainability disclosure of food and beverages companies listed in Indonesia stock exchange in 2021-2023. The variables used in the research are sustainability disclosure as an dependent variable, as well as corporate government components include audit committee activities, board of commissioners independence, board of directors size, institutional ownership and also company characteristic include leverage and firm size as the independent variables. Secondary data is used in this research and multi-case study sampling is used as the sampling technique. The difference between this research and the previous one is that the sample used in this research is food and beverage companies listed on Indonesian Stock Exchange in 2021-2023 with the total samples being 117 samples. The research results show that variables of audit committee activities, board of commissioners independence and firm size have a positive effect on sustainability dislosure. board of directors size and institutional ownership have a negative effect on sustainability disclosure. This research also proves that leverage does not significantly affect on sustainability disclosure.